Changes In Different Forms Of K In Rice Rhizosphere Under K Application (Bangladesh Journal of Agricultural Research, 2011)
A pot experiment was conducted with four soils from two locations (BAU farm, Mymensingh and BADC farm, Madhupur, Tangail) in order to monitor the transformation of added K (soil solution K, exchangeable K+ and nonexchangeable K) in BRRI dhan-41 rhizosphere at saturation condition. There were six levels of K viz., 0, 30, 60, 90,120 & 150 kg/ha from MoP. Eight kg soil was taken into each pot. The K concentration in soil solution increased with increasing K addition and decreased with increasing incubation period. Soil solution K was drastically reduced at 45 days due to higher crop uptake. The amount of exchangeable K also increased with increment of added K and gradually decreased over time. The non-exchangeable K increased up to 45 days and then decreased up to 105 days. Keywords: Rice rhizosphere; exchangeable K+; non-exchangeable K DOI: http://dx.doi.org/10.3329/bjar.v36i3.9279 BJAR 2011; 36(3): 513-519